Decoupled Evolution between Senders and Receivers in the Neotropical Allobates femoralis Frog Complex - Betancourth-Cundar, Mileidy (PLoS One, 2016)
During acoustic communication, an audible message is transmitted from a sender to a receiver, often producing changes in behavior. In a system where evolutionary changes of the sender do not result in a concomitant adjustment in the receiver, communication and species recognition could fail. However, the possibility of an evolutionary decoupling between sender and receiver has rarely been studied. Frog populations in the Allobates femoralis cryptic species complex are known for their extensive morphological, genetic and acoustic variation. We hypothesized that geographic variation in acoustic signals of A. femoralis was correlated with geographic changes in communication through changes in male-male recognition. To test this hypothesis, we quantified male call recognition using phonotactic responses to playback experiments of advertisement calls with two, three and four notes in eight localities of the Amazonian basin. Then, we reconstructed the ancestral states of call note number in a phylogenetic framework and evaluated whether the character state of the most recent common ancestor predicted current relative responses to two, three and four notes. The probability of a phonotactic response to advertisement calls of A. femoralis males was strongly influenced by the call mid-frequency and the number of notes in most populations. Positive phonotaxis was complete for calls from each individual's population, and in some populations, it was also partial for allotopic calls; however, in two populations, individuals equally recognized calls with two, three or four notes. This evidence, in conjunction with our results from phylogenetic comparative methods, supports the hypothesis of decoupled evolution between sender and receiver in the male-male communication system of the A. femoralis complex. Thus, signal recognition appears to evolve more slowly than the calls.